A Case of Pulmonary Tumor Thrombotic Microangiopathy Diagnosed by Transbronchial Lung Biopsy and Treated with Chemotherapy and Long-Term Oxygen and Anticoagulation Therapies - Atsushi Kitamura; Naoki Nishimura; Torahiko Jinta; Rika Suda; Yasuhiko Yamano; Genta Ishikawa; Yutaka Tomishima; Tsuyoshi Hamaoka; Koyu Suzuki; Naohiko Chohnabayashi (Case Reports in Pulmonology)
A 41-year-old woman, who underwent breast resection for cancer of the right breast and adjuvant chemotherapy 2 years ago, was admitted to our hospital due to shortness of breath upon exertion. High-resolution computed tomography of the chest showed small nodular opacities in the peribronchiolar area in both lungs, as well as mediastinal and hilar lymphadenopathy. A transbronchial lung biopsy revealed breast cancer metastasis and pulmonary tumor thrombotic microangiopathy (PTTM). Treatment of PTTM is rarely reported due to the difficulty of antemortem diagnosis; however, the patient was effectively treated with chemotherapy and oxygen and anticoagulation therapies for 3 months.